Stochastic calculus of variations for jump processes - Ishikawa, Yasushi, 1959 October 1- (De Gruyter studies in mathematics ;, 2016)
This monograph is a concise introduction to the stochastic calculus of variations for processes with jumps. It is written for researchers and graduate students who are interested in Malliavin calculus for jump processes. The author provides many results on this topic in a self-contained way. The book also contains some applications of the stochastic calculus for processes with jumps to the control theory and mathematical finance.